Distributed trust model based on parameter modeling - Jing-pei WANG; Bin SUN; Xin-xin NIU; Yi-xian YANG (Tongxin xuebao)
A distributed trust model based on parameter modeling was posed.Nine functional parameters were extracted after investigating the trust mechanism and current trust models.These parameters included flexibility,subjectivity,fuzziness,time decay property,transitivity,anti-attacks property,rewards ＆amp; punishment property,sensitivity and scalability.Each parameter was modeled and integrated to form a comprehensive trust model.Analytical results indicate that the proposed trust model satisfies all the nine functional parameters and thus has fair universality Experimental results show that the proposed trust model is reasonable and effective.Comparisons with previous algorithms indicate that the performance of the proposed trust model has been improved.